Effect of immersion treatment of fibre on mechanical properties of putruded kenaf vinyl ester composites - Mohamad, Nur Marliana (2016)
Recently, a traditional materials such as metal, ceramic, plastic and wood which have served in engineering applications for a long time are being substituted by the natural composite materials. The natural composite materials seem to be advantages over the traditional material in their recyclability, sustainability, easy to obtain and cheap, easy and low cost of production and environmental friendly. Despite the natural fibre composite have many advantages but it also have the limitation high moisture absorption compare to syntetic composites. The purpose of this research is to compare the mechanical properties of kenaf and glass pultruded vinyl ester composites and to determine the effect of immersion in sea water, distilled water and acidic solutions on mechanical properties of kenaf pultruded vinyl ester composites. The specimens of the kenaf composites were produced using pultrusion machine and immersed in various solution such as sea water, distilled water and acidic solution. The specimen tested using mechanical testing such as tensile, flexural and impact test. These studies have been done in order to evaluate the strength, stiffness, and toughness behaviour of kenaf reinforced vinyl ester composites as which is can be used as replacement of raw materials for the reinforcement of polymer matrix composites The mechanical properties of the kenaf and glass pultruded composites has been carried out to compare the performance of the kenaf pultruded over the glass pultruded which is shown a largely used in commercials. The results of tensile strength of the glass and kenaf pultruded 248.1 and 148.5 MPa, tensile modulus 14.1 and 12.3 GPa, flexural strength 322.2 and 185.5 MPa, flexural modulus 5.3 and 2.03 GPa and impact energy 274.73 and 59.71kJ/m2 respectively. The results on the effect of immersion in acidic, sea water and distilled water on mechanical properties of kenaf pultruded reinforced vinyl ester composites shows that sea water has the smallest reduction of tensile strength, flexural strength and impact strength, were decreased from 1st, 2nd and 3rd weeks. Acidic solution shows the highest reduction of the properties of tensile strength, flexural strength and impact strength due to the highest degradation on the pultruded composites.